2021
DOI: 10.3390/ijerph181910519
|View full text |Cite
|
Sign up to set email alerts
|

The Intersections of Ethnicity, Nativity Status and Socioeconomic Position in Relation to Periodontal Status: A Cross-Sectional Study in London, England

Abstract: The role of migration as a social determinant of periodontitis has been overlooked. Intersectionality theory could help understand how immigration status interacts with other social determinants of health to engender inequalities in periodontitis. The objective of the present study was to evaluate whether ethnicity, nativity status and socioeconomic position intersect to structure social inequalities in periodontal status. Data from 1936 adults in a deprived and multi-ethnic area of London were analysed. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…A subsequent metanalysis that included seven longitudinal studies with sample sizes ranging from 167 to 2806 subjects found that lower life‐long socioeconomic position increased the risk of periodontitis in adulthood 37 . A recent cross‐sectional study involving 1936 adults in London demonstrated that periodontitis was associated with individual and intersectional social characteristics, especially ethnicity and education 38 . Another cross‐sectional study of Indian adults also identified ethnicity as a risk indicator for periodontitis 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent metanalysis that included seven longitudinal studies with sample sizes ranging from 167 to 2806 subjects found that lower life‐long socioeconomic position increased the risk of periodontitis in adulthood 37 . A recent cross‐sectional study involving 1936 adults in London demonstrated that periodontitis was associated with individual and intersectional social characteristics, especially ethnicity and education 38 . Another cross‐sectional study of Indian adults also identified ethnicity as a risk indicator for periodontitis 39 .…”
Section: Discussionmentioning
confidence: 99%
“…37 A recent cross-sectional study involving 1936 adults in London demonstrated that periodontitis was associated with individual and intersectional social characteristics, especially ethnicity and education. 38 Another cross-sectional study of Indian adults also identified ethnicity as a risk indicator for periodontitis. 39 While the present study did not examine educational status, the results affirm that periodontitis is significantly associated with both race and ethnicity for adults seeking dental care in rural communities in North Carolina.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in the Celeste et al 43 study on the Brazilian population, the moderate to severe periodontitis weighted prevalence was not significantly different between ethnicity in both low‑ and high‐income groups. The Shaharyar et al 44 studyon the multi‐ethnic population of East London did not find a significant interaction between ethnicity, nativity, and socioeconomic status. Ethnic diversity is an advantage for studies in which interactions between socioeconomic status and race/ethnicity is of interest.…”
Section: Cross‐sectional Studiesmentioning
confidence: 84%
“…The results of this study showed that income and education might affect periodontitis via independent pathways. 43 Shaharyar et al 44 Mendelian randomization is a method of using observational data to measure the causal exposure effects on a particular outcome. In recent years genome-wide association studies were used to obtain large-scale genetic association data for Mendelian randomization analysis.…”
Section: >6 Ymentioning
confidence: 99%
See 1 more Smart Citation